Adnexial Mass in the Adolescents - Evrim Erdemoğlu; İlker Günyeli; Mansur Kamacı; Tamer Mungan (Medical Network, 2011)
OBJECTIVE: is to investigate features of adnexial masses required emergency or elective operations in the adolescents. We analyzed the features, presentation of adnexial masses and their management in young adolescent women in a referral hospital. STUDY DESIGN: We have retrospectively analyzed patients admitted to two different department of Obstetrics and Gynecology between 2005- 2006 and 2009-2010. Patients included to study were at or under the age of twenty and had gynecological operation for adnexial mass. RESULTS: Thirty two of 879 (3.6%) gynecological procedures were in adolescents under the age of twenty. Adnexial masses were the leading cause of these gynecological procedures compromising 81.2% (n=26) of adolescents' gynecological procedures. Fifty percent of operations (n=13) were in the emergency setting. Laparotomy to laparoscopy ratio was 2.2. Operations for a benign pathology consisted of 84%. Sixteen percent of all cases and 19% of ovarian masses were malignant. Use of ultrasonography and laboratory examination correctly led to diagnosis of benign cases. CONCLUSION: In adolescents laparoscopy and conservative surgery are choice of operation and every effort should be undertaken to perform them. Preoperative evaluation of adnexial mass in the adolescents could be made correctly.